Approach to the Effects of Greek Regional Universities on Development of the Country Regions - Yiota Theodora (European Regional Science Association (ERSA), 2006)
Although the start of the debate on the contribution of universities to the local and regional development dates back to several decades ago, it is only in the past 25 years that it has been intensified and seen from a new angle of investigation and consideration. It is therefore imperative that the "higher education – development" relationship be reviewed and placed on different basis. The causes for this is the major change in the content of "development" and the concept of "university" [mainly in terms of its role in the society and economy], the new policies and socio-economic conditions globally, the contemporary weight attributed to new technologies and knowledge dissemination as a "development factor", as well as the large number of unsuccessful attempts to use the universities a "means" for development. In the context of this general consideration at global level, it is investigated whether the Greek regional universities- as they have been established, allocated, organized and operating- have played, and may play, some part in the development of the broader areas [region, town]. In other words, it is investigated whether the expansion of higher education institutions throughout Greece has contributed to the improvement of the education quality standard and resolution of the country's "regional problem". The approach to this question is based on the grounds of two principal pursuits. First, it is studied whether and how the expansion of university education has been used as a "means of development" at the principal stages of the country's "regional development" [1946-1999]. It is, therefore, investigated whether the policy on regional universities planning and establishment was integrated in the broader framework of policies on development and education, also taking into account the regional and local specificities, needs and capabilities. Second, it is studied which are the main "operational factors" that seem to have influenced the development role of regional universities and the relationship of the latter with local societies. The implementation of the study was based on the investigation of the relevant international and Greek bibliography, and on a series of surveys focusing on : a) the Greek planning system for "development", "spatial", "regional policies" and their association with "higher education" and b) the entirety of regional universities [8 universities, 1999] and cities - prefecture capitals of Greece [53], placing special emphasis on the seventeen university-cities [2003].
Keywords: 330